Network disruption detected in CU (Cuba) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Cuba. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: CU-2026-0003. Severity: critical. Confidence: 65%